Effect Of Female Students In Mixed Class On The Educational Achievement Of The Class At Mechanical Techniques Department – Basrah Technical Institute – Southern Technical University - Abdulsamad Albachri, Sabah (Opción, 2019)
The present study aimed to identify the effect of the presence of female stu- dents in the mixed class on the level of general achievement in the Department of Mechanical Techniques at the Technical Institute in Basra, and is there any statistically significant differences in general judgment. The research commu- nity consisted of (216) students from the Mechanical Production Department who were successful in the first to second grades of the two sexes, and were divided into four equal divisions but there was 2 divisions mixed and other separated. The overall success rate for the academic year 2017 - 2018 for both groups was extracted from the exam committee records, after the names were withheld for the confidentiality of the exam committee. average in the mixed group (62.65) which is less than average success in single sex which was (63.75%) and females in the mixed classes (74.04) were found to be close and did not make a statistically significant difference after the T test. In light of its objectives, the present research has reached the following results: 1 - The presence of female students does not lead to raising the level of overall achievement of the Mixed Education Division, and the success rates are simi- lar. 2 - There are no statistically significant differences between the two types of co-educational and single sex. 3 - The mixed education has advantages and disadvantages of both sexes in the same division, and was addressed in the main body of research. 4 - Co-education does not constitute a burden on the teaching and administration of the department Send feedback.